2015
DOI: 10.4103/1735-9066.164513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the alert line of partogram in recognizing the need for neonatal resuscitation

Abstract: Background:A major problem of the first moments of childbirth, especially in “prolonged labor,” is perinatal asphyxia which necessitates neonatal resuscitation. This study aimed at evaluating the alert line of the partogram in recognizing the need for neonatal resuscitation 20–30 s after delivery.Materials and Methods:140 full-term pregnant women were kept under surveillance through using a partogram. In order to decide on the onset of resuscitation, the three indicators of fetal respiration, heart rate, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Many studies were from urban settings (urban: n = 16, rural: n = 1, both: 2), for 18 studies this could not be determined. Studies were on: admission tests and early intrapartum (CTG, n = 7, IA: 1, other methods, n = 6) [ 32 35 , 44 , 48 , 51 , 56 , 57 , 59 , 61 ], ongoing intrapartum FHR monitoring (IA, n = 8; CTG, n = 11) [ 26 28 , 30 , 31 , 36 39 , 41 , 43 , 45 47 , 50 , 53 , 58 ], adjunctive tests (n = 9) [ 39 , 41 – 43 , 45 , 46 , 49 , 52 , 58 ] and partograph (n = 5) [ 24 , 25 , 29 , 40 , 54 , 55 ] (Tables 1 – 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies were from urban settings (urban: n = 16, rural: n = 1, both: 2), for 18 studies this could not be determined. Studies were on: admission tests and early intrapartum (CTG, n = 7, IA: 1, other methods, n = 6) [ 32 35 , 44 , 48 , 51 , 56 , 57 , 59 , 61 ], ongoing intrapartum FHR monitoring (IA, n = 8; CTG, n = 11) [ 26 28 , 30 , 31 , 36 39 , 41 , 43 , 45 47 , 50 , 53 , 58 ], adjunctive tests (n = 9) [ 39 , 41 – 43 , 45 , 46 , 49 , 52 , 58 ] and partograph (n = 5) [ 24 , 25 , 29 , 40 , 54 , 55 ] (Tables 1 – 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Training midwives to use the partograph reduced low Apgar scores at 1 minute but no improvement in other perinatal outcomes [ 29 ]. Observational studies showed that crossing the alert and action lines on the partograph was associated with a higher incidence of neonatal resuscitation and fresh stillbirths [ 54 , 55 ]. Substandard use of partograph was associated with low Apgar score [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, correctness and completeness of recordings of parameters on partographs was determined by appropriate documentation of 13 (Mandiwa & Zamawe, 2017 ) variables. These were; assessment of the mother for potential risk factors, recording of foetal heart rates every half hour, recording of the intactness or rupture of membranes, recording of colour of liquor upon rupture of membranes, recording of foetal head moulding, recording of cervical dilation every four (Bolbol‐Haghighi et al, 2015 ) hourly, recording of uterine contractions every half hourly, recording of foetal descent every two hourly, recording of maternal temperature every 4‐hourly, recording of maternal pulse rate every half hourly, recording of maternal blood pressure every 4‐hourly, urine testing for proteins and a recording of actions taken when needed. All the 13 variables were scored with either Yes (1) or No (0).…”
Section: The Studymentioning
confidence: 99%